Clinical outcomes and hospital readmission rates in mechanical vs bioprosthetic mitral valves. Issue 7 (24th May 2019) - Sultan, Ibrahim; Bianco, Valentino; Gleason, Thomas G.; Aranda‐Michel, Edgar; Navid, Forozan; Kilic, Arman
Abstract: Objective: Recent national trends have demonstrated increased use of bioprosthetic mitral valves. The primary objective of this study was to compare clinical outcomes as well as readmission rates for mechanical vs bioprosthetic mitral valve replacement (mMVR vs bMVR). Methods: All patients undergoing MVR from 2011‐2017 were included in a single center data set that was obtained retrospectively from a prospectively maintained cardiac surgical database. Results: The total MVR patient cohort consisted of 828 patients, including bMVR (n = 522) and mMVR (n = 306). There was no significant difference in the operative (30‐day) mortality between bMVR and mMVR (8.6% vs 6.5%; P = .31). The unadjusted estimated 1‐year mortality was significantly higher for the bMVR group (19.8% vs 13.7%, P = .04) and this trend continued for the estimated 5‐year mortality (35.1% vs 18.7%; P = .001). Valve prosthesis choice (bMVR vs mMVR) did not have a risk‐adjusted impact on operative mortality at 30 days ( P = .58); however 1‐year ( P = .05) and 5‐year ( P = .05) mortality remained significantly higher for the bMVR group. Propensity matching revealed a higher mortality rate on follow‐up in the bMVR (26.7% vs 18.2%, P = .03) but no difference at 30 days or 1 year. There was no difference in hospital readmissions over 5 years Conclusions: Mechanical prostheses may confer a survival benefit in patients undergoing MVR. With emphasis on patient education and anticoagulation compliance, mMVR remains an efficacious option.